Alcohol Intake Interacts with CDKAL1, HHEX, and OAS3 Genetic Variants, Associated with the Risk of Type 2 Diabetes by Lowering Insulin Secretion in Korean Adults. (3rd October 2018) - Park, Sunmin; Liu, Meiling; Kang, Suna
Abstract : Background: Since alcohol intake increases the prevalence of type 2 diabetes (T2DM) in Koreans, we tested the hypothesis that the interactions of genetic variants involved in β‐cell function and mass with alcohol intake increase the T2DM risk. Methods: The single nucleotide polymorphisms (SNPs) were selected by genome‐wide association study for insulin secretion after adjusting for age, gender, area of residence, body mass index, and alcohol intake ( p < 1 × 10 −4 ) in 8, 842 middle‐aged adults in the Ansan/Ansung cohort. Genetic risk scores (GRSs) were calculated by summing the risk alleles of 4 selected SNPs, CDKAL1 rs7754840 and rs9460546, HHEX rs5015480, and OAS3 rs2072134. The GRSs were categorized into 3 groups by tertiles, and the association between GRS and insulin secretion was measured using logistic regression after adjusting for confounding factors in the Ansan/Ansung cohort. The results were confirmed by the Rural cohort. Results: HOMA‐IR was higher and HOMA‐B was much lower in the High‐GRS than the Low‐GRS in both cohorts. T2DM risk was higher by approximately 1.5‐fold in the High‐GRS than in the Low‐GRS in both cohorts. In the High‐GRS group, HOMA‐B decreased by 0.89‐ and 0.62‐fold in comparison with the Low‐GRS in the Ansan/Ansung cohort and Rural cohort. The GRS interacted with alcohol intake to increase the risk of developing T2DM in the Ansan/Ansung cohort ( p = 0.036) and Rural cohort ( p = 0.071). The risk of T2DM increased in the High‐GRS group with high alcohol intake and it was associated with decreased HOMA‐B. High alcohol intake decreased HOMA‐B regardless of GRS, and HOMA‐B was lower in the descending order of Medium‐GRS, Low‐GRS, and High‐GRS. However, HOMA‐IR was not altered by alcohol intake, but was elevated in the High‐GRS more than in the other groups. Conclusions: Subjects with a High‐GRS had an elevated risk of T2DM even with moderate alcohol intakes due to lower HOMA‐B. High alcohol intake appears to be a risk factor for all Asians regardless of alcohol intake. Abstract : This research evaluated the effects of a high genetic risk score (GRS) for low insulin secretory capacity and alcohol consumption on the risk of developing type 2 diabetes (T2DM). High alcohol intake and a high GRS resulted in a much greater risk for T2DM. However, subjects with a High‐GRS had an elevated risk of T2DM even with moderate alcohol intake due to lower HOMA‐B. High alcohol intake appears to be a risk factor for all Asians regardless of GRS.